Book Reviews. (1st September 2018) - Clarke, Margaret Anne; Rendeiro, Margarida; Wheeler, Duncan; Crameri, Kathryn; Magone, José M.; Tang, Wan Sonya
Salazar: Portugal e o Holocausto, Irene Flunser Pimentel and Claúdia Ninhos (2013) 1st ed., Lisbon: Circular de Leitores e Temas e Debates, 928 pp., ISBN 9-789-89644-221-7, p/bk, €24.40A História da PIDE, Irene Flunser Pimentel (2011) 7th ed., Lisbon: Circular de Leitores e Temas e Debates, 575 pp., ISBN 9-789-72759-956-1, p/bk, €19.90A Cada Um O Seu Lugar: A Política Feminina do Estado Novo, Irene Flunser Pimentel (2011) 1st ed., Circular de Leitores e Temas e Debates, 455 pp., ISBN 9-789-89644-143-2, p/bk, €5.00The Making of Modern Portugal, Luís Trindade (ed.) (2013) Newcastle upon Tyne: Cambridge Scholar Publishing, 318 pp., ISBN (10) 1-4438-5039-X, h/bk, £49.99; ISBN (13) 978-1-4438-5039-1Social Movements and the Spanish Transition: Building Citizenship in Parishes, Neighbourhoods, Schools and the Countryside, Tamar Groves, Nigel Townson, Inbal Ofer and Antonio Herrera (2017) Cham: Palgrave Macmillan, xvii + 144 pp., ISBN 978-3-31961-835-7, h/bk, €57.19; ISBN 978-3-31961-836-4, ebook, €44.02The Rise of Catalan Independence: Spain's Territorial Crisis, Andrew Dowling (2018) Abingdon; New York: Routledge, 194 pp., ISBN 9-781-47245-984-8, h/bk, £115; ISBN 9-781-13858-770-0, p/bk, £29.99Iberian Elites and the EU: Perceptions towards the European Integration Process in Political and Socioeconomic Elites in Portugal and Spain, Miguel Jerez-Mir, José Real-Dato and Rafael Vázquez-García (eds) (2016) Granada: University of Granada, 244 pp., ISBN 978-8-43385-838-2, p/bk, €20Historia de lo Fantástico en la Cultura Española Contemporánea (1900–2015), David Roas (dir.) (2017) Madrid/Frankfurt: Iberoamericana/Vervuert, 386 pp., ISBN 9-788-41692-201-7, p/bk, €29.80/32.00